"BEYOND THE BOOKS: ASSESSING DIGITAL LITERACY COMPETENCE IN TODAY'S STUDENTS" - Wan Hashridz Rizal bin Wan Abu Bakar,; Ainuddin bin Kamaruddin,; Siti Masliah Mohd Nuri,; Mohamad Hasmimie Mohd Yusof, (Journal of Islamic, Social, Economics and Development, 2023)
This research endeavors to investigate and evaluate the digital literacy competence of present-day students, recognizing the growing importance of technological skills in contemporary education. The study employs a comprehensive approach to gauge students' proficiency in digital literacy. The objective of this study is to evaluate the digital literacy competence of contemporary students according to the factors that have been selected. This research through content analysis research design are used. Data collected from materials such as books, journal articles and descriptive proceedings. This study found that aspects of students' digital literacy are influenced by four factors, namely gender, age, students' digital media experience and parents' educational background. Furthermore, the research highlights the need for an integrated approach to digital literacy within the education system. As technology continues to evolve, educators and policymakers must collaborate to bridge gaps in current educational practices and develop effective digital literacy programs.